Building a family within a non-heterosexual couple: Struggles, fears, representations and practices - Santos, F.; Dias, R. (Childbearing and the changing nature of parenthood: The contexts, actors, and experiences of having children, 2020)
In the twenty-first century, the family has been turning towards a greater plurality of training paths, situations, family and parental arrangements. However, despite changes in legislation, values, representations and practices, the word family remains inexorably associated with the heterosexual bi-parental model. This paper aims to contribute to the knowledge of the family dynamics of non-heterosexual people, mainly concerning the process of transition to parenting, in relation to family changes in Portuguese society. To do so this study aims to analyze four in-depth interviews with young adults, women and men who have a homoconjugality relationship and a project of parenting in mind. Based on a qualitative methodology the study intends to discuss issues related to the challenge of heteronormativity, equality within the couple, projects and gender representations of parenthood and in particular what it means for the men and women interviewed, to be a father and to be a mother in a same sex couple and how they project themselves as fathers and mothers. The study discusses all these issues always in relation to the biographical trajectories, the history and life as a couple and the structural and individual resources, such as school and professional qualifications. It also analyzes the main difficulties experienced in revealing their sexuality to the significant others and the difficulties / strategies they anticipate in relation to the parenting project. The authors conclude that female interviewees show greater independence of a male figure in relation to their parental projects and anticipate less difficulty in their parental skills compared with the gay man interviewed. To analyze the dynamics of parenting in same-sex couples, this study also points out to the need to construct a model of analysis capable of articulating structural factors, such as job insecurity and heteronormativity, biographies and individual resources and profiles of conjugal interactions.